Mathematical evolution in discrete networks - Pfaltz, John F. (Vysoké učení technické v Brně, Fakulta strojního inženýrství, Ústav matematiky, 2013)
This paper provides a mathematical explanation for the phenomenon of \triadic closure" so often seen in social networks. It appears to be a natural consequence when network change is constrained to be continuous. The concept of chordless cycles in the network's \irreducible spine" is used in the analysis of the network's dynamic behavior. A surprising result is that as networks undergo random, but continuous, perturbations they tend to become more structured and less chaotic.